FEMINIST REIMAGINING IN FAIR ROSALINE: NATASHA SOLOMONS’ REVISION OF ROMEO AND JULIET THROUGH HAROLD BLOOM’S REVISIONARY RATIOS - Emanuelle, Glory; Zahroh, Adiba Qonita (Elite : English and Literature Journal, 2024)
The growing inclusivity in today’s literary world offers female writers the chance to explore a wide range of themes even those that were previously considered exclusive for male writers. It led to the re-examination and reinterpretation of classic literature through a feminist lens. This study seeks to provide a comprehensive analysis of Natasha Solomons’ Fair Rosaline through the lens of Harold Bloom’s “Revisionary Ratios.” This paper employs mainly qualitative research design by combining textual analysis and comparative literary criticism to explore Natasha Solomons’ Fair Rosaline as a feminist reinterpretation of Shakespeare’s Romeo and Juliet through the lens of Harold Bloom’s “Revisionary Ratios” theory and feminism literary theory. The texts of Fair Rosaline and Romeo and Juliet serve as the primary data. Not only that this research adds to the larger discussion concerning the place of women in literature while also improving our understanding of Fair Rosaline and its connection to Romeo and Juliet, but also offers new insights into how feminist writers reimagine classical texts and empower female narratives with new, critical perspectives.